Improving the TPACK Competence of Prospective Physics Teachers Through the Use of the Nearpod Application - Muhammad Yakob; Mentari Darma Putri; Chairuddin; Mursyida; Asrama Rizki Lubis (CV Media Inti Teknologi, 2026)
Purpose of Study: This study aims to examine the effectiveness of Nearpod-based training in improving the Technological Pedagogical Content Knowledge (TPACK) competence of prospective physics teachers in designing physics learning tools.Methodology: This study employed a quantitative approach with two analytical components. The first component used a One-Group Pretest–Posttest design involving 19 prospective physics teachers who participated in Nearpod-based training and teaching simulations. The second component involved a final TPACK questionnaire administered to 60 prospective physics teachers from four universities. Data were analyzed using N-Gain, the Wilcoxon Signed-Rank Test, and the Rasch Model with Winsteps software. Main Findings: The results showed that the mean TPACK score increased from 76.05 in the pre-test to 91.50 in the post-test, with an N-Gain value of 0.65, indicating moderate improvement. The Wilcoxon test produced a significance value of 0.000, confirming a statistically significant difference between pre-test and post-test scores. Rasch analysis showed that 85% of respondents were in the moderate TPACK category. The Wright Map further indicated that Technological Knowledge, Content Knowledge, and some aspects of Pedagogical Knowledge were relatively easier to master, whereas Pedagogical Content Knowledge, Technological Pedagogical Knowledge, and holistic TPACK remained more challenging.Novelty/Originality of This Study: This study highlights Nearpod not only as a digital learning platform, but also as a pedagogical design space that supports prospective physics teachers in integrating physics content, interactive digital features, formative assessment, student engagement, and feedback within technology-enhanced learning.